2011
DOI: 10.5012/bkcs.2011.32.7.2428
|View full text |Cite
|
Sign up to set email alerts
|

A Regiospecific One-Pot, Three Component Synthesis of 4-Aryl-6,8-dimethylpyrimido[4,5-c]pyridazine-5,7(6H,8H)-diones as New Potential Monoamine Oxidase Inhibitors

Abstract: A series of new 4-aryl-6,8-dimethylpyrimido[4,5-c]pyridazine-5,7(6H,8H)-diones have been synthesized via three component reaction of 1,3-dimethylbarbituric acid with arylglyoxals in the presence of hydrazinium dihydrochloride in ethanol. All of these derivatives may act as potential monoamine oxidase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Consequently, MCRs have emerged as a powerful tool for delivering molecular libraries needed in combinatorial approaches for the assembly and lead identification of bioactive compounds. [21] Based on the above considerations and in continuance of our previous research into the arylglyoxal-mediated synthesis of various heterocycles, [22][23][24][25][26][27][28][29][30][31][32] we have found that 1,3-dialkyl thiobarbituric acids undergo a tandem Knoevenagel-Michael condensation with arylglyoxals leading to the formation of a substituted pyranopyrimidine skeleton. Herein, we report an efficient two-component strategy for synthesis of symmetrically substituted 5-aryloyl-1H-pyrano[2,3-d]pyrimidine 1.…”
Section: Introductionmentioning
confidence: 94%
“…Consequently, MCRs have emerged as a powerful tool for delivering molecular libraries needed in combinatorial approaches for the assembly and lead identification of bioactive compounds. [21] Based on the above considerations and in continuance of our previous research into the arylglyoxal-mediated synthesis of various heterocycles, [22][23][24][25][26][27][28][29][30][31][32] we have found that 1,3-dialkyl thiobarbituric acids undergo a tandem Knoevenagel-Michael condensation with arylglyoxals leading to the formation of a substituted pyranopyrimidine skeleton. Herein, we report an efficient two-component strategy for synthesis of symmetrically substituted 5-aryloyl-1H-pyrano[2,3-d]pyrimidine 1.…”
Section: Introductionmentioning
confidence: 94%
“…Morrison and co‐workers were described the cyclizations of glyoxals with 6‐hydrazinoisocytosines while the synthesis of 3‐(substituted)pyrimido[4,5‐ c ]pyridazine‐5,7(1 H ,6 H )‐diones were performed by Turbiak through the condensation of 3‐methyl‐6‐(1‐methylhydrazinyl)uracil with phenyl and alkyl glyoxal monohydrates . A series of new 4‐aryl‐6,8‐dimethylpyrimido[4,5‐ c ]pyridazine‐5,7(6 H ,8 H )‐dione derivatives were synthesized via three component reactions of 1,3‐dimethylbarbituric acid with arylglyoxals in the presence of hydrazinium dihydrochloride .…”
Section: Introductionmentioning
confidence: 99%
“…7 Hence, the synthesis of pyridazine derivatives has been studied for many years. [8][9][10][11][12][13][14] In continuation of recent reports on synthesis of pyridazine derivatives, [15][16][17][18][19][20][21][22][23] we would like to report the single crystal X-ray structure of 3-amino-5-(4-chlorophenyl)pyridazine-4-carbonitrile prepared by a one-pot three-component reaction of malononitrile with corresponding arylglyoxal in the presence of hydrazine hydrate at room temperature. 23 …”
Section: Introductionmentioning
confidence: 99%